The Assessment by Small and Medium Entrepreneurs of the Usefulness of Tools Used for the Diagnosis and Prognosis of the Economic Situation - Kowerski, Mieczysław; Bielak, Jarosław; Długosz, Dawid (Regional Barometer. Analyses & Prognoses, 2009)
The article presents the findings of a research survey concerning the use by the entrepreneurs the analysis of a local economic situation, and the use of tools allowing to predict the condition of one’s own company in comparison with other regional companies that are in the same business. A detailed statistical analysis of the collected data, as well as binary and ordered dependent variable models, which unable to evaluate the usefulness of the tools that have been described in the paper, are also presented.